Adapting the current mass mobilization approach in Ethiopia to enhance its impact on sustainable land management: Lessons from the Sago-kara watershed. (15th October 2019) - Abi, Meskerem; Kessler, Aad; Oosterveer, Peter; Tolossa, Degefa
Abstract: This paper analyses the effect of an adapted – more participatory and more integrated – mass mobilization training approach on Ethiopian farmers' motivation to practice integrated farming and invest in Sustainable Land Management (SLM). It is based on the results of an experiment carried-out in the Sago-kara watershed in the Central highlands of Ethiopia, in which a group of 26 farmers received an adapted training at the start of the mass mobilization campaign in 2016, which aimed to strengthen farmers' knowledge and awareness about natural resource management, drought mitigation and integrated farm planning. One year later, both qualitative and quantitative data were collected through group discussions, field observations and household surveys. For the before-after comparison we used descriptive statistics to analyze the data; the with-without comparison (with a control group) differences were statistically tested at 1% and 5% probability levels. The results show that the adapted training approach enhanced awareness of farmers, created motivation for integrated farm management and fostered implementation of SLM practices in the field. Most interesting is that farmers who followed the training better plan for drought mitigation and are more aware of the possible effects of drought on their farming activities. The study concludes that the current mass mobilization approach in Ethiopia can have more impact on SLM if it would pay serious attention to: 1) creating awareness on the causes and effects of erosion and drought focusing on sustainability issues, 2) fostering farmers' intrinsic motivation to be good stewards of their land; 3) training in integrated farm planning, and 4) developing farm plans based on farmers' visions for resilient farming. In order to make agricultural extension in Ethiopia more effective, one has to start with capacity building of the rural extension staff in participatory training methods, followed by empowering and motivating farmers for SLM. This will not only lay a foundation for sustainable agriculture and more food security on the farm, but is also crucial for the scaling-up of resilient farming to watershed and landscape levels in Ethiopia. Highlights: Participatory training and learning significantly increases motivation for integrated farm management. Training in integrated farming significantly increases implementation of SLM practices. Integrated farm management increases soil fertility and food security. Empowering and motivating farmers lays a foundation for sustainable agriculture.